2009
DOI: 10.1007/s12160-009-9113-8
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Post-Action Stages of the Transtheoretical Model to Predict Change in Regular Physical Activity: A Multiethnic Cohort Study

Abstract: The TTM post-action stages had limited usefulness in this cohort. Further longitudinal study is needed to determine whether TTM stages can accurately classify transitions from physical inactivity to physical activity below recommended levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Observational studies of community adults have reported that both cognitive and behavioral processes were related to maintenance of moderate [66] or vigorous [67] physical activity. However, adherence in those studies was determined using self-reports of action and maintenance stages, which have modest agreement with maintenance of regular moderate or vigorous physical activity sufficient for public health [68]. …”
Section: Discussionmentioning
confidence: 99%
“…Observational studies of community adults have reported that both cognitive and behavioral processes were related to maintenance of moderate [66] or vigorous [67] physical activity. However, adherence in those studies was determined using self-reports of action and maintenance stages, which have modest agreement with maintenance of regular moderate or vigorous physical activity sufficient for public health [68]. …”
Section: Discussionmentioning
confidence: 99%
“…A cohort of 497 participants completed the measures at least three times and was used for analysis; 468 completed the measures four times and 394 completed them all five times. The cohort did not differ from the total random sample on physical activity or demographics reported elsewhere [44]. Characteristics of the cohort were: 63.6% female; 31.8% Asian; 19.3% Native Hawaiian/Pacific Islander; 39.8% Caucasian; 8.0% Other (African American, Mexican, Puerto Rican, American Indian, Mixed non-Hawaiian); 52.9% Married; mean age=48.8 years, SD=16.7, range=18–90; mean education=15.0 years, SD=2.9; median income=$40,000 to $50,000)…”
Section: Methodsmentioning
confidence: 99%
“…Participants provided self-reports of gender, age, race/ethnicity, years of education, household income, marital status, height, and weight, which have been described elsewhere [44]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations